Nursing and anthropology in Brazil: relations, dilemmas and challenges - Lucas Pereira de Melo (Universidad de Alicante, 2013)
Taking as a starting point to finding the invisibility of nursing scientific production in anthropological perspective on the literature reviews on anthropology of health in Brazil, the aim of this essay is to make a brief critical discussion of nursing and anthropology punctuating the particularities of the Brazilian context compared with countries like United States, England and Spain, and especially discuss the dilemmas (problems and limits) in the relations existing between the two disciplines and indicate some challenges to its development and consolidation. Finally, the enrollment of the arguments and comparative analysis of building this relationship in different countries allowed viewing certain hypotheses that aim to contribute to future discussions and studies in Brazil.